2004
DOI: 10.1038/sj.hdy.6800477
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between fitness and heterozygosity at allozyme and microsatellite loci in the Atlantic salmon, Salmo salar L.

Abstract: The relationship between heterozygosity at genetic markers (six allozyme and eight microsatellite loci), and fluctuating asymmetry (FA), length and weight was investigated in two samples of Atlantic salmon (Salmo salar L.) with different timings of first active feeding (early (EA) and late (LA) salmon). This trait had previously been related to fitness. EA fish show smaller values of FA, are longer, heavier and are more heterozygous at allozyme loci than are conspecific LA fish. Also within both samples, heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 51 publications
(73 reference statements)
2
52
1
1
Order By: Relevance
“…The question of the genetic factors governing developmental stability is still far from being settled. Although first microsatellite analyses did not produce a negative correlation between FA and variability (Borrell et al, 2004), our results show that further research into the relative role of key loci and overall genomic heterozygosity is required.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The question of the genetic factors governing developmental stability is still far from being settled. Although first microsatellite analyses did not produce a negative correlation between FA and variability (Borrell et al, 2004), our results show that further research into the relative role of key loci and overall genomic heterozygosity is required.…”
Section: Resultsmentioning
confidence: 82%
“…This is important because it is still an open question if the relationship between developmental stability and genetic variability (if there is any at all) is due to the physiological properties of specific enzymes encoded by certain key loci or owing to overall genomic heterozygosity. Our results based on microsatellites, which are non-coding DNA regions commonly regarded as selectively neutral, favour the latter alternative (against Kruuk et al, 2003 andBorrell et al, 2004) although linkage with key loci can never totally be ruled out. It has to be borne in mind, however, that all genetic parameters calculated in our study are based on eight loci only, which is probably not enough to be representative of genome-wide heterozygosity (see Chakraborty, 1981;Slate and Pemberton, 2002).…”
Section: Fe Zachos Et Almentioning
confidence: 69%
See 2 more Smart Citations
“…In accordance with the review of Chapman et al (2009), previous reviews concluded that if HFCs exist, they will be better detected by individual heterozygosity than by d 2 values (Tsitrone et al 2001;Slate & Pemberton 2002;Coltman & Slate 2003). MLH has also been the metric used in most HFC studies on fish (Drahushchack 1990;Ferguson 1992;Pogson & Fevolden 1998;Thelen & Allendorf 2001;Borrell et al 2004;Lieutenant-Gosselin & Bernatchez 2006), including the only study to date reporting positive HFCs on European eel (Pujolar et al 2005), in which the positive associations found at MLH contrasted with the lack of association using d 2 measurements. Previous studies in which d 2 outperformed MLH seems to be restricted to species with particular inbreeding patterns (harbour seal, Coltman et al 1998;red deer, Coulson et al 1998) that do not apply to the outbred European eel.…”
Section: Discussionmentioning
confidence: 88%